Pengaruh Lingkungan dan Nilai Ripitabilitas pada Kualitas Semen Sapi Peranakan Ongole Jantan - Gunawan Sitanggang (Institut Pertanian Bogor, 2018)
The aims of this study were to analyze the effect of environmental factors (age of bull, season of collection and frequency of ejaculation) and estimate the repeatability on semen quality of ongole grade bulls. Semen data were collected from Singosari National Artificial Insemination Centre, in Malang District, East Java Province, Indonesia. A total of 1.020 ejaculates collected from three Ongole grade cattle from 2012-2016 were analyzed. Data were analyzed by restricted maximum likelihood (REML) method using the mixed model including the random effect of bull and the fixed effects of age of bull, season of collection, and ejaculate number. The results showed that age of bull and ejaculate number significantly affected all studied variables (P<0.01). Season only affected to sperm motility (P<0.01). Repeatability estimates of semen volume, sperm concentration, total number of sperm and sperm motility were 0.48; 0.42; 0.28; and 0.01, respectively. It was concluded that the age of the bull and frequency of ejaculation significantly affected semen quality of Ongole grade cattle. Repeatabilities for semen quality were low, moderate and high.